A prática docente frente ao individualismo e consumismo na infância pós-moderna: concepção dos professores do Ensino Fundamental - Bianca Ferreira Rocha (2014)
The present study aimed to investigate and analyze the conceptions of teachers in the early grades of elementary school regarding their practice about consumerism and individualism in post- modern childhood. In order to achieve the objectives proposed in this paper, a qualitative research of theoretical and empirical data was performed. Data collection in the field was conducted through semi - structured interviews with four teachers who teach in elementary education at a municipal school in Belo Horizonte. Data were analyzed based on content. It was observed that the concept of childhood is guided by the image of innocence, naivety and immaturity, according to the teachers. Consumerism was mentioned as a feature that is present in today's childhood, which was not observed about individualism. However, it was pointed out by the teachers that socialization and interactions that children establish with themselves have changed and they are associated with consumption. In this context, teachers can realize the importance of working these issues that arise in relationships between children. Therefore, discuss about the conceptions that teachers have about their practice about consumerism and individualism in post- modern childhood, allows us to understand more about how childhood is seen and worked in a school context and which educational practices are privileged in that space.